Antibacterial resin monomers based on quaternary ammonium and their benefits in restorative dentistry - Satoshi Imazato; Ji-hua Chen; Sai Ma; Naomi Izutani; Fang Li (Elsevier, 2012)
Antibacterial resin monomers are unique molecules that provide dental resins with "bio-active function", i.e. the ability to control bacterial infection. They have strong antibacterial activity when unpolymerized and also demonstrate contact inhibitory effects after being polymerized without releasing antibacterial components. Intensive research has been conducted on antibacterial monomers based on quaternary ammonium, such as methacryloyloxydodecylpyridinium bromide (MDPB), focusing on their basic properties and uses in several resinous restoratives. As represented by successful commercialization of an adhesive system incorporating MDPB, quaternary ammonium based antibacterial monomers have the potential for utilization in various restorative materials and regimens, including caries management and pulp care.